The law of habeas corpus - Farbey, Judith; Sharpe, Robert J.; Atrill, Simon (Oxford : Oxford University Press, 2011)
Habeas corpus is everyone's 'get out of jail free' card. It is the legal remedy ensuring a person's release from prison or any other form of custody when the detention cannot be justified in law. This volume provides in-depth and critical analysis of the law behind this vital protection of liberty.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Habeas corpus -- England; Habeas corpus -- Wales